2004
DOI: 10.1111/j.0022-202x.2004.23313.x
|View full text |Cite
|
Sign up to set email alerts
|

The Osmolyte Strategy of Normal Human Keratinocytes in Maintaining Cell Homeostasis

Abstract: Compatible organic osmolytes, such as betaine, myoinositol, and taurine, are involved in cell volume homeostasis as well as in cell protection, for example, against oxidative stress. This so-called osmolyte strategy requires the expression of specific osmolyte transporting systems such as the betaine/gamma-amino-n-butyric acid (GABA) transporter, the sodium-dependent myoinositol transporter and the taurine transporter (TAUT). In contrast to liver, kidney, and neural cells, nothing is known about osmolytes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 49 publications
(59 reference statements)
3
90
0
1
Order By: Relevance
“…For the patients with diabetes mellitus, they are likely to be in high osmotic pressure condition since the level of glucose in the blood is high. In the condition of high osmotic pressure, it is reported that mRNA expression of TauT, betaine transporter (BGT-1) and sodium/myo-inositol co-transporter (SMIT) is changed and uptake of taurine, betaine and myo-inositol is elevated in many tissues (Warskulat et al, 1997;Takeuchi et al, 2000;Shioda et al, 2002;El-Sherbeny et al, 2004;Warskulat et al, 2004). Moreover, there are some papers that the mRNA expression of TauT and BGT-1 and the uptake of taurine and betaine into the kidney elevated under high osmotic pressure (Uchida et al, 1992;Yamauchi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For the patients with diabetes mellitus, they are likely to be in high osmotic pressure condition since the level of glucose in the blood is high. In the condition of high osmotic pressure, it is reported that mRNA expression of TauT, betaine transporter (BGT-1) and sodium/myo-inositol co-transporter (SMIT) is changed and uptake of taurine, betaine and myo-inositol is elevated in many tissues (Warskulat et al, 1997;Takeuchi et al, 2000;Shioda et al, 2002;El-Sherbeny et al, 2004;Warskulat et al, 2004). Moreover, there are some papers that the mRNA expression of TauT and BGT-1 and the uptake of taurine and betaine into the kidney elevated under high osmotic pressure (Uchida et al, 1992;Yamauchi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high abundance in tissues, and its manifold functions in cellular homeostasis, little is known until now about the role(s) of the osmolyte taurine in skin cells (15,35). Prompted by our finding that uptake of taurine and expression of the transporter for taurine, TAUT, are up-regulated by UVB exposure in keratinocytes (15), we studied whether taurine deficiency in the skin of mice influences their susceptibility to UVB-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard we have recently shown that epidermal keratinocytes possess an osmolyte strategy, i.e., upon exposure to hyperosmotic stress keratinocytes accumulate the osmolyte taurine (15). In these studies, taurine uptake was associated with an increased expression of the specific transporter for taurine, i.e., TAUT.…”
mentioning
confidence: 98%
“…GABA most probably also plays a role in the physiology of keratinocytes, and is observed within the keratinocyte [40][41][42]. One of the enzymes involved in the synthesis of GABA has been identified in the skin [43].…”
Section: Potentiation Of Gabamentioning
confidence: 99%